2016
DOI: 10.1186/s12916-016-0716-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artemether-lumefantrine in relation to drug exposure in children with and without severe acute malnutrition: an open comparative intervention study in Mali and Niger

Abstract: Background: Severe acute malnutrition (SAM) affects almost all organs and has been associated with reduced intestinal absorption of medicines. However, very limited information is available on the pharmacokinetic properties of antimalarial drugs in this vulnerable population. We assessed artemether-lumefantrine (AL) clinical efficacy in children with SAM compared to those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
(38 reference statements)
1
28
0
Order By: Relevance
“…While the common seasonality of malaria and malnutrition has been previously documented [ 8 ], the presence of a biological or immunological interaction between malaria and malnutrition that may encourage a high burden of both diseases remains unclear [ 9 , 10 ]. It has been suggested that malnutrition may predispose children to infection or make it more difficult to recover from infection [ 8 , 11–14 ]; however, the epidemiological evidence is mixed [ 15–25 ]. At the same time, malaria infection may predispose a child to acute weight loss or impair response to standard treatment for malnutrition [ 11 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the common seasonality of malaria and malnutrition has been previously documented [ 8 ], the presence of a biological or immunological interaction between malaria and malnutrition that may encourage a high burden of both diseases remains unclear [ 9 , 10 ]. It has been suggested that malnutrition may predispose children to infection or make it more difficult to recover from infection [ 8 , 11–14 ]; however, the epidemiological evidence is mixed [ 15–25 ]. At the same time, malaria infection may predispose a child to acute weight loss or impair response to standard treatment for malnutrition [ 11 ].…”
mentioning
confidence: 99%
“…It has been suggested that malnutrition may predispose children to infection or make it more difficult to recover from infection [ 8 , 11–14 ]; however, the epidemiological evidence is mixed [ 15–25 ]. At the same time, malaria infection may predispose a child to acute weight loss or impair response to standard treatment for malnutrition [ 11 ]. Previous studies have shown malaria infection to be associated with poor nutritional status [ 26–30 ].…”
mentioning
confidence: 99%
“…Although two of these studies [20,22] considered reinfections as treatment successes in their calculation of PCR-corrected e cacy (an approach not consistent with WHO guidelines), the e cacy results remained above 97% when recalculating e cacy using the WHO-endorsed approach of eliminating reinfections from the calculation. E cacy results above 90% were reported in another Mali study [23], conducted in 2013-2015, although this study reported combined results in children from another country, Niger, in addition to Koulikoro, Mali. Similar to the AL day 28 uncorrected e cacy of 83.4% in our study, the two other Mali-exclusive studies that examined day 28 uncorrected e cacy reported results of 83.8% and 84.5% [20,22].…”
Section: Discussionmentioning
confidence: 55%
“…There has been limited information on the effect of malnutrition on the PK and therapeutic responses after ACTs in malnourished children or adults. Day 7 lumefantrine concentration following artemether‐lumefantrine in severe acute malnutrition is about 70% that of individuals without severe acute malnutrition 172 . Therapeutic efficacy in both groups are shown to be similar, but the risk of reinfection is higher in older children with severe acute malnutrition due to lower drug exposure.…”
Section: Antimalarial Dose Optimization In Special Conditionsmentioning
confidence: 97%